The Determinants of Part-Time Work in EU Countries : Empirical Investigations with Macro-Panel Data - Hielke Buddelmeyer; Gilles Mourre; Melanie E. Ward (Institute for the Study of Labor (IZA), 2004)
This paper aims to identify the contribution of the business cycle and structural factors to the development of part-time employment in the EU-15 countries, through the exploitation of both cross-sectional and time series variations over the past two decades. Key results include that the business cycle is found to exert a negative effect on part-time employment developments. This is consistent with firms utilising part-time employment as a means of adjusting their labour force to economic conditions. Correspondingly, involuntary part-time employment is found to be countercyclical, being higher in troughs of economic activity. Splitting our sample reveals a very significant effect of the business cycle on the rate of part-time work for young and male prime-age workers. Conversely, the effect is very weak for women and insignificant for older workers. Institutions and other structural factors are also found to be significant and important determinants of the rate of part-time employment. Changes in legislation to part-time employment are found to be effective, having a strong and positive impact on part-time employment developments. Moreover, employment protection legislation is positively correlated with the part-time employment rate, which is consistent with the use of part-time work as a tool for enhancing flexibility in the presence of rigid labour markets. Less robust evidence suggests the presence of unemployment traps for some potential part-time workers. Cross-country evidence also indicates that the lower labour costs borne by firms when employing part-time workers has a large and positive influence on the part-time employment rate.
Keywords: J22; J68; J21; 330; part-time employment; working time organisation; business cycle; labour supply; labour market policies; institutions; regulations; Teilzeitarbeit; Beschäftigungseffekt; Konjunktur; Industriestruktur; Institutionelle Infrastruktur; Arbeitslosenversicherung; Familienleistungsausgleich; Frauenerwerbstätigkeit; Ältere Arbeitskräfte; Jugendliche Arbeitskräfte; EU-Staaten